Strategy In Realizing Sustainable Performance Management At PT. Pegadaian Tanjungpinang Branch - Deri Satria; Asyuara Ionantamelia P; Lisa Anisa Agustiani; Qonita, 5Satriadi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to explore strategies for realizing sustainable performance management at PT. Tanjungpinang Branch Pawnshop. This research uses qualitative research through data collection, observation and interviews. The sampling technique used was purposive sampling. The informant is Mr. HR as Marketing Officer. The data analysis used in this research is descriptive analysis, namely the researcher collects, processes and analyzes data to describe the problems that exist at PT Pegadaian Tanjungpinang Branch. The research results show that the strategy applied at PT. Pegadaian Tanjungpinang Branch in realizing sustainable performance management, namely the digitalization strategy of Human Resources and Talent Management. In this case, the Human Resources digitalization strategy includes transforming the Human Resources Management system through digital platforms, increasing employee skills in technology, using data for strategic decision making, and implementing an adaptive technology-based work culture. Meanwhile, talent management includes recruitment planning and appropriate individual selection, as well as skills development through training and mentoring.